The Impact of Types of Institutional on Market Liquidity - Nadia BELKHIR (Communications of International Proceedings, 2023)
This paper investigates the roles institutional investors play in a representative emerging market, focusing on the relationship between institutional ownership and stock market liquidity in Saudi Arabia. In particular, we examine the relation between stock liquidity and institutional ownership by type of institution. The expected impact of insurance companies on liquidity is ambiguous. On the one hand, institutional investors as insurance companies are considered to have access to private information about the firm because either they have resources to make analyses on the firm and acquire information. Hence, increased institutional ownership should lead to wider spreads and higher adverse selection costs. Market makers are made to expand the spread and thus they would be forced to own a larger inventory position in stocks with a higher institutional ownership. These factors explain the negative impact of institutional ownership on liquidity. On the other hand, institutional investors are indirect, and their investment policy is to hold diversified portfolios that compensate them.
Keywords: liquidity; institutional investors; insurance companies; bid ask spread; depth; lambda.